2010
DOI: 10.1177/0898264310373502
|View full text |Cite
|
Sign up to set email alerts
|

Lifelong Educational Practices and Resources in Enabling Health Literacy Among Older Adults

Abstract: Findings are discussed in relation to the development and maintenance of health literacy over the life course. Programs and policies that encourage lifelong and lifewide educational resources and practices by older persons are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
56
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 25 publications
4
56
0
1
Order By: Relevance
“…4 More recently there has been an attempt to apply this model to understanding predictors of health. Wister and colleagues, 17 for example, used the expanded Andersen-Newman model -which included lifelong educational practices and resources as enabling factors -and found that formal education and lifelong learning factors were the variables to have the strongest connection with health literacy.…”
Section: Introduction Theoretical Frameworkmentioning
confidence: 99%
“…4 More recently there has been an attempt to apply this model to understanding predictors of health. Wister and colleagues, 17 for example, used the expanded Andersen-Newman model -which included lifelong educational practices and resources as enabling factors -and found that formal education and lifelong learning factors were the variables to have the strongest connection with health literacy.…”
Section: Introduction Theoretical Frameworkmentioning
confidence: 99%
“…It has been applied to other types of behavior, however [70], particularly involving organizational features as enabling factors [25,71,72].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that older adults are predisposed to low literacy including health literacy (Wister et al 2010). Educated older adults who read more often are better able to process information on health practices and healthy lifestyles (Roberts and Fawcett 2003); and this gives them an edge with respect to a healthy and successful aging process (O'Rand and Hamil-luker 2005;Wister et al 2010). As Baker et al (2007) agued, adults with high functional literacy are less likely to die than those with low functional literacy.…”
Section: The Challenges Of the Elderly In Nigeriamentioning
confidence: 99%
“…This shows that health literacy is very vital to sustaining the quality of life. This is so because it helps in the understanding of the risks and benefits involved in medical treatments, and in the sustenance of a healthy lifestyle as well as a better self-management of illness (Canadian Council on Learning 2007; Wister et al 2010). What this suggests is that 'older adults who read manuals, reference books, or journals to learn and those who use the computer or internet to learn are more likely to be health literate than those not engaging in these types of learning practices' (Wister et al 2010: 846).…”
Section: The Challenges Of the Elderly In Nigeriamentioning
confidence: 99%